Cephisus siccifolia (Walker) (Hemiptera: Aphrophoridae): description of the immature and adult stages, including genital morphology, with notes on species delimitation challenges in the genus - Domahovski, Alexandre Cruz; Alasmar, Luísa; Barão, Kim Ribeiro; Paladini, Andressa (Zootaxa, 2025)
Aphrophoridae is a worldwide distributed family, most diverse in the tropics and less represented in the Holartic region, including 157 genera and 925 species. The New World genus Cephisus currently comprises eight described species which are strongly homogeneous morphologically but have a considerable degree of intraspecific variation. Cephisus siccifolia is a species of potential economic interest which was recorded as a pest in cultures of Eucalyptus spp. in the state of Bahia, Brazil. Herein we describe and illustrate for the first time, in detail, the male and female genitalia of C. siccifolia as well as the immature stages from specimens collected on Tipuana tipu (Fabaceae) in the state of Paraná, Southern Brazil. A morphometric analysis is presented based on seven morphometric parameters to test measurements that can accurately help discriminate each nymphal stage. We also illustrate genital and general morphologic variations of Cephisus siccifolia and Cephisus spp., including specimens of a wide geographic sample, discussing the impacts of morphologic variation to the taxonomy of the genus and problems in species delimitation.